Conception of forming of marketing strategy of development of the strictly specialized machine-building enterprises - V.J. Bytsa (Marketing i Menedžment Innovacij, 2011)
In the article the basic theoretical going is considered near development and realization of marketing strategy of the strictly specialized machine-building enterprises; the stages of forming of strategy are described; the complex of economic problems of realization of strategic marketing approach is exposed at the market of the special industrial to the products.